Regulation of the Regulators: Post-Translational Modifications, Subcellular, and Spatiotemporal Distribution of Plant 14-3-3 Proteins - Wilson, Rashaun S.; Swatek, Kirby N.; Thelen, Jay J. (Frontiers in Plant Science, 2016)
14-3-3 proteins bind to and modulate the activity of phosphorylated proteins that regulate a variety of metabolic processes in eukaryotes. Multiple 14-3-3 isoforms are expressed in most organisms and display redundancy in both sequence and function. Plants contain the largest number of 14-3-3 isoforms. For example, Arabidopsis thaliana contains thirteen 14-3-3 genes, each of which is expressed. Interest in the plant 14-3-3 field has swelled over the past decade, largely due to the vast number of possibilities for 14-3-3 metabolic regulation. As the field progresses, it is essential to understand these proteins’ activities at both the spatiotemporal and subcellular levels. This review summarizes current knowledge of 14-3-3 proteins in plants, including 14-3-3 interactions, regulatory functions, isoform specificity, and post-translational modifications. We begin with a historical overview and structural analysis of 14-3-3 proteins, which describes the basic principles of 14-3-3 function, and then discuss interactions and regulatory effects of plant 14-3-3 proteins in specific tissues and subcellular compartments. We conclude with a summary of 14-3-3 phosphorylation and current knowledge of the functional effects of this modification in plants.